1992
DOI: 10.7863/jum.1992.11.6.263
|View full text |Cite
|
Sign up to set email alerts
|

Normal and respiratory variations of the hepatic and portal venous duplex Doppler waveforms with simultaneous electrocardiographic correlation

Abstract: To understand hepatic vein (HV) and portal vein (PV) duplex waveforms and their normal and respiratory variations, HV and PV duplex sonography with simultaneous electrocardiograpy was performed on 11 volunteers. Absolute velocities of the waveforms' components and their ratios were determined at mid· in· spiration, full inspiration, full expiration, and Valsalva maneuver. The normal HV waveform was variable in shape and component velocities and ratios but essentially consisted sequentially of (1) an antegrade … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
70
0
1

Year Published

1996
1996
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(73 citation statements)
references
References 1 publication
2
70
0
1
Order By: Relevance
“…Contraction of the abdominal muscles during expiration aids venous return in mammals (Abel and Waldhausen, 1969;Youmans et al, 1963). In contrast to the inspiratory increase in IAP, intrathoracic and right atrial pressures decrease during inspiration in mammals, increasing blood flow in the veins located near the thorax, such as the jugular and hepatic veins and the superior vena cava (Abu-Yousef, 1992;Brecher and Hubay, 1955;Brecher and Mixter, 1953;Mixter, 1953;Moreno et al, 1967;Osada et al, 2002;Takata et al, 1992;Teichgraber et al, 1997;Willeput et al, 1984).…”
Section: Discussionmentioning
confidence: 99%
“…Contraction of the abdominal muscles during expiration aids venous return in mammals (Abel and Waldhausen, 1969;Youmans et al, 1963). In contrast to the inspiratory increase in IAP, intrathoracic and right atrial pressures decrease during inspiration in mammals, increasing blood flow in the veins located near the thorax, such as the jugular and hepatic veins and the superior vena cava (Abu-Yousef, 1992;Brecher and Hubay, 1955;Brecher and Mixter, 1953;Mixter, 1953;Moreno et al, 1967;Osada et al, 2002;Takata et al, 1992;Teichgraber et al, 1997;Willeput et al, 1984).…”
Section: Discussionmentioning
confidence: 99%
“…The portal flow signal was obtained in the main portal trunk before its division into the right and left branches according to previously published protocols. 8 …”
Section: Doppler Ultrasonographic Recordingsmentioning
confidence: 99%
“…7 Normal PV flow profile is less well understood. 8 Because of the interposed liver, portal venous flow is not in phase with the cardiac cycle and is more influenced by respiration (Figure 1). Like Arisawa et al, 7 we found increased pulsatility in both APC and TCPC groups.…”
Section: Flow Profilesmentioning
confidence: 99%
“…The phasicity is caused by the changes in cardiac cycle, predominantly the change in right atrial pressure [5]. Its correlation with electrocardiographic tracing further advocates cardiac origin.…”
Section: Discussionmentioning
confidence: 93%
“…However, change of waveform to biphasic from triphasic seems suggestive of some changes in the liver parenchyma as only cirrhotic patients showed change from triphasic to biphasic or flat waveform. Although the phasicity is cardiac in origin, respiratory motion can alter the HV waveforms and its components [5]. With Valsalva maneuver and suspended respiration, the negative oscillation disappeared in few cases and it may be the reason of discrepancy in findings among many studies.…”
Section: Discussionmentioning
confidence: 95%